The pattern of problematic internet use and mental health-related internet use among psychiatric outpatients at a tertiary care center - Yatan Pal Singh Balhara; Swarndeep Singh; Rachna Bhargava (Tzu Chi Medical Journal)
Objective: There is scarce literature available on the pattern of problematic internet use (PIU) and use of internet for mental health help-seeking among adult patients with psychiatric disorders in South-East Asian countries. The present study aimed to understand the pattern of PIU among adult patients attending the outpatient psychiatry services at a tertiary care center in India. Further, it aimed to explore the use of internet for seeking mental health-related information or services among them. Materials and Methods: This cross-sectional study recruited adult outpatients attending the outpatient psychiatry services following purposive sampling between June 2018 and December 2018. A semi-structured questionnaire was used to collect information regarding sociodemographic characteristics and internet use pattern of participants, including use of internet for various mental health-related purposes. The Generalized Problematic Internet Use Scale 2 (GPIUS-2) was used to assess the PIU. Statistical analysis was performed using SPSS version 23.0 software. Results: Among 155 study participants, 45 (29.03%) scored above 60 on GPIUS-2. Those with PIU were significantly younger, reported higher duration of daily internet use, and spent greater proportion of time online on activities related to social networking or social media than those with and without PIU. More than half of the participants reported internet use for seeking mental health-related information at least once in the past 1 month. There was no significant difference in the mental health-related internet use among adult patients with different psychiatric diagnoses, except for two situations. There was lesser use of internet for seeking information related to the symptoms of illness and various treatment modalities available among participants diagnosed with psychotic disorder. On the other hand, a greater use of internet for seeking information related to the symptoms of illness was reported by participants diagnosed with anxiety disorder. Conclusion: This study suggested that PIU is a frequently cooccurring condition among adult patients with primary psychiatric disorder. The importance of internet as a medium for seeking mental health information and services was observed among most of the study participants.